2003
DOI: 10.1351/pac200375020369
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomics approach to the study of triterpene biosynthesis

Abstract: The Arabidopsis thaliana genome-sequencing project has identified the presence of 13 oxidosqualene cyclase homologs in this plant. In addition to the already identified clones, namely, CAS1 cycloartenol synthase, LUP1 lupeol synthase, and YUP8H12R.43 multifunctional triterpene synthase, two new cDNAs of the putative oxidosqualene cyclase genes, F1019.4 and T30F21.16, were obtained by polymerase chain reaction (PCR) and functionally expressed in yeast. Liquid chromatography/mass spectrometry (LC/MS) analysis le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 8 publications
1
57
0
Order By: Relevance
“…16) No OSC yielding aamyrin as a sole product has been reported and all OSCs whose products include a-amyrin are multifunctional. They are OEA from O. europaea (this study), PSM from Pisum sativum, 17) At1g78960 18) and At1g78500 19,20) from Arabidopsis thaliana, KcMS from Kandelia candel, 21) and two OSCs from Taraxacum officinale (our unpublished results). Furthermore, most of the phytochemical studies reported the presence of ursane type triterpenes together with oleanane type triterpenes.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…16) No OSC yielding aamyrin as a sole product has been reported and all OSCs whose products include a-amyrin are multifunctional. They are OEA from O. europaea (this study), PSM from Pisum sativum, 17) At1g78960 18) and At1g78500 19,20) from Arabidopsis thaliana, KcMS from Kandelia candel, 21) and two OSCs from Taraxacum officinale (our unpublished results). Furthermore, most of the phytochemical studies reported the presence of ursane type triterpenes together with oleanane type triterpenes.…”
mentioning
confidence: 63%
“…Some callus cultures produce no trace of the metabolites found in the mother plants but produce those metabolites that are not produced by the mother plants. This situation is exemplified by Glycyrrhiza glabra cell cultures, which did not produce glycyrrhizin (18), a major triterpene saponin of the mother plant, but produced betulinic acid (16) 8) and soyasaponin I (19). 9) It is quite interesting to know what kinds and how much of triterpenes cultured cells produce.…”
mentioning
confidence: 99%
“…Although 13 OSC genes were identified in the Arabidopsis thaliana genome, 31) five OSC genes, which have been functionally identified, encode one cycloartenol synthase 32) and four multifunctional triterpene synthases, 31,[33][34][35] respectively. The multifunctional triterpene synthase produces multi-triterpene-products from 2,3-oxidosqualene, the common substrate for OSCs, and this type of OSC was also cloned from pea, 36) Costus speciosus 37) and Lotus japonicus.…”
Section: Discussionmentioning
confidence: 99%
“…A selected number of genes are provided in Table 2 and include those involved in both aliphatic and aromatic metabolic pathways associated with suberin formation. Genes potentially linked with suberin biosynthesis found to be downregulated in both myb9 and myb107 seeds include those encoding SUS (the putative suberin synthase); an SGNH hydrolase-type esterase superfamily protein (likely involved in lipid metabolic processes; Li-Beisson et al, 2013); CASP-LIKE PROTEIN 1B2 (CASPL1B2, showing strong homology to CASP proteins involved in casparian strip metabolism); LACCASE3 (a member of the laccase family of which LACCASE4 has been demonstrated to be involved in lignin metabolism; Zhao et al, 2013;Schuetz et al, 2014); DIHYDROFLAVONOL 4-REDUCTASE-LIKE1 (DFR-like1; involved in phenylpropanoid metabolism and previously linked to pollen wall development and seed production (Lallemand et al, 2013); and LUPEOL SYNTHASE5 (LUP5; a multifunctional triterpene synthase; Ebizuka et al, 2003). While genes downregulated in myb107 seeds (but not myb9 seeds) encode GPAT5 and ASFT (known to act in suberin formation); 3-KETOACYL-COA SYNTHASE17 (KCS17; a very-long-chain fatty acid synthase); 4-COUMARATE:COA LIGASE5 (4CL5; involved in phenylpropanoid metabolism); and GLYCOSYLPHOSPHATIDYLINOSITOL-ANCHORED LIPID PROTEIN TRANSFER5 (LTPG5; a homolog to the lipid transporter LTPG1; Debono et al, 2009;Edstam and Edqvist, 2014).…”
Section: Myb107 and Myb9 Are Required For Suberin-associated Gene Expmentioning
confidence: 99%